Urgensi Soft skill dalam Perspektif Teori Behavioristik - I Putu Suardipa; I Ketut Widiara; Ni Made Indrawati (STAHN Mpu Kuturan Singaraja, 2021)
The point is that a person has a sense, a conscience that must be developed to be able to govern himself or herself and to interact with others. Pedagogic competence is the ability of a teacher in processing the learning process of learners. In addition, pedagogic skills are also shown in helping, guiding, and leading learners who can implicitly cultivate the soft skills of learners. A teacher is able to master the characteristics of learners, master the theory of learning, utilize information technology in learning, and perform reflective actions to improve the quality of learning and provide intrapersonal and interpersonal abilities so that mature personalities are formed in learning. In summary Intrapersonal skills include Self a wareness and Self skill, while interpersonal skills include social a wareness and social skills. It becomes its own urgency in the order of maturity of the child into the future regeneration. Keywords: Soft Skill, Behavioristic Theory